Kajian Tarif Karcis Dan Keterlambatan Kereta Api Kelas Ekonomi Lintas Jogjakarta â Jakarta Terhadap Kinerja Pt. (Persero) Kereta Api (Studi Kasus Pada Kereta Api Kelas Ekonomi Empu Jaya) - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2002)
ABSTRAK Train passengers, especially in economic and business class, often complain the tendency of poor service provided by (Persero) Kereta Api, especially for reliability and punctuality level. The frequent delays increase operational costs with effect on profit. If it continueus, the company will suffer loss. This research predicts the operational cost for a single trip of Jakarta-Jogjakarta, as well as additional cost caused by trip delay per time unit. This value is obtained by identifying the direct operational cost (Biaya Operasional Langsung = BOL), indirect operational cost (Biaya Operasional Tidak Langsung = BOTL) as well as other additional costs influencing the train trip. This study uses the train performance data from the Center Office of PT (Persero) Kereta Api , Kantor DAOP VI Yogyakarta and DAOP I Jakarta as well as interview survey results of passengers and coordinators of Empu Jaya Ecenomic Class Train The result of this study shows that the normal operational cost for Jakarta-Yogyakarta trip is Rp 18,760,111 (Rp 20,935/pasenger) with an assumption that all of the 896 tickets are sold out through legal ticket counter. Considering the current tariff, which is Rp 24,000 per passenger, the company gains profit of Rp 3,064 (12.77%) per person for a single trip. The normal operational cost includes BOL of Rp 14,235,393 (75.88%), BOTL of Rp 3,607,041 (19.23%), and other costs of Rp 917,676 (4.9%). Trains with delays may non-linearly increase the operational cost of Rp 33,850/minute of delays. If the delay is more than 108 minutes (Â± 1 hour and 48 minutes), the company may not gain any profit. The standard occupancy level for KA Empu Jaya is 87.24%. If the occupancy level is 87.24% and all of the 782 tickets are sold out through legal lockets, this service is profitable. On the other hand, if the occupancy level is under this value, the service may suffer loss. Keywords:kinerja PT Persero KA, tarif KA